Tingkat Pengetahuan Diabetes Melitus Warga Pondok Bambu - Haryo Ganeca Widyatama; Dietha Kusumaningrum; Alvina Dwi Susanti; Inaya Larang Asri; James Bernando Rajagukguk; Mesty Mela Safitri; Edy Parwanto (CV. Multi Kreasi Media, 2024)
Diabetes is a chronic metabolic disease, characterized by increased blood sugar levels. There are two types of diabetes mellitus, type 1 and type 2. Complications of diabetes mellitus consist of macrovascular, such as coronary heart disease, stroke, and peripheral vascular disease, and microvascular, such as neuropathy, nephropathy, and retinopathy. It is said to be diabetes if the blood sugar test is ≥ 200 mg/dL and pre-diabetes if the result is ≥ 140 mg/dL. Meanwhile, checking fasting blood sugar ≥ 126 mg/dL, HbA1c > 6.5%, G2PP ≥ 199 mg/dL can also be said to be diabetes. The prevalence of diabetes in Indonesia is highest in Jakarta, namely 3.4%. East Jakarta itself is in second place in terms of diabetes sufferers in Jakarta. With the high rate of diabetes in Jakarta, especially East Jakarta, this community service is carried out which aims to increase public knowledge about diabetes mellitus. The Community Service Method this time uses the lecture method by the material presenter. There was an increase in knowledge about diabetes mellitus after the intervention.